(3ebOeI aj QhGjI MaUs - (3GdOefghQj , CMeO Hf YHO GdefYe Hf jhSa Hf UjGe GdOefghQj, SQGL GdOjf,J (B1192 (3g` s
(3ChdgG (B:s
(3hHYO agPg ebOeI CfjbI aGFbI QbjbI MGhjI QhGjI MaU hTYHI ef WQjb GdMQR s
(3BNQgG (B:s
(3bGd GdNGJe jYfj ddbQBf haj gPG GdbOQ caGjI hGddg JYGdi CYde HGdUhGH JeJ gPg GdebOeI HMeO Gddg hYhfg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B164 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B303s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCRgQjI (B((3bQGAGJ (B296) s
Keywords: (3GdbQGAGJ hGdJLhjOs